The Drivers of the Information Revolution : Cost, Computing Power, and Convergence - Bond, James (World Bank, Washington, DC, 2012)
The author explains the drivers of the information revolution - the decline in the cost of transmitting information, the increase in the power of computing, and the shift from analog to digital information technologies that has joined the telecommunications and computing industries and merged segments of the information industry. Over the past twenty years, the cost of voice transmission circuits and the computing power per dollar invested have both fallen by a factor of 10,000. Prices have not fallen nearly as fast - they have been set by a cartel-like system of international agreements between incumbent monopolies. But as convergence restructures the telecommunications industry, new operators are arbitraging the difference between costs and the old tariff structures, putting pressure on incumbent telecommunications operators.